Driving Safety Assurance Method in Work Zone Crossovers of Highway Reconstruction and Expansion Project - Lu Lv; Yanting Sheng; Cancan Song; Yongqing Li; Zhongyin Guo (Journal of Advanced Transportation)
Work zone crossover is an important area in highway reconstruction and expansion projects because it profoundly impacts the traffic safety and efficiency of the construction sites. This research sets the different median opening widths in the driving simulation experiment, collects the vehicle control signal parameters during entrance by-pass and exit by-pass, and analyzes the driving characteristics in these sections. Comparison of the driving features between the simulation experiment and the actual driving under the same median width has been also made. We should set the median width separately because the results show that driving behaviors significantly differ between entrance by-pass and exit by-pass. When the median opening width is 70 m, the driving simulation experiment and actual driving characteristics are quite different. However, both show that driving factors of the entrance and exit by-pass are not the same. When there are two lanes in the traffic control zone and the speed limit is 60 km/h, we should set the median width at 90 m to ensure transportation safety.